Share Price Reactions to CEO Departure Announcements Event Study - Eduard Lechner, Markus Johann (2004)
This study examines the share price reactions to Chief Executive Officer (CEO) departure announcements of firms listed on share markets in the United States. Most announcements include additional new information about the firm, which represents a contamination that needs to be accounted for. Share price reactions to CEO departures are moderate. Non-contaminated announcements have no significant (-0.40%) market reactions. Investors show stronger reactions to new information related to the firm compared to new information related to the CEO. Announcements that include criticism of the departing CEO have average abnormal returns of +3.33%. A temporary arrangement for the CEO position following the departure has negative average abnormal returns of -3.57%. Statements that express that a CEO leaves for personal reasons are acknowledged with -3.90% average abnormal returns. New information about firms that represents bad news causes average abnormal returns of -7.91%. Earnings related information in announcements is appreciated with -7.76% average abnormal returns. The 177 observations are divided into numerous subgroups to test 17 hypotheses related to the CEO, the firm, and circumstantial factors. The entire content of the announcements is examined for share price reaction in order to achieve a complete, reliable and meaningful interpretation of share price movements on the event day. The results support the main hypothesis that CEO departure announcements have neutral market reactions. Investors pay most attention to firm related information included in a CEO departure announcement.